PROSPEK PURUN (Eleocharis sp) SEBAGAI HASIL HUTAN BUKAN KAYU UNTUK MENDUKUNG EKONOMI MASYARAKAT SEKITAR HUTAN RAWA GAMBUT - Indrayanti, Lies; Elvina, Elvina; Nuwa, Nuwa; Nursiah, Nursiah; Yanarita, Yanarita; Ludang, Yetri; Misrita, Misrita (Agrienvi: Jurnal Ilmu Pertanian, 2023)
Purun is one of the Non-Timber Forest Products that comes from peat swamp forests. This plant grows wild and is used by communities around the forest to make various handicraft products as a side income. This research aims to analyze Purun's prospects as an NTFP to support the economy of communities around peat swamp forests. There are three research locations, namely Petuk Katimpun Village, Kalampangan Village, and Tumbang Nusa Village. The sampling method was purposive sampling, namely people who were purun craftsmen and lived close to the purun growing area. Data analysis uses SWOT analysis. The research results show that the prospect of Purun as a non-timber forest product (NTFP) to support the economy of communities around peat swamp forests in the three research locations is in a strategic position, namely at the cut-off point (0.569; 0.684), precisely in the first quadrant (I). The alternative strategy used is the SO (Strength and opportunities) strategy, namely utilizing Purun NTFPs; creating markets and promotions; increasing Human Resources (HR) through training and forming Micro, Small and Medium Enterprises (MSME) groups. Based on these results, the policy that is expected is to support the use of Purun NTFPs by the community, by providing counseling, training and outreach so that Purun Purun products can compete with other NTFP products.